1993
DOI: 10.1126/science.8493555
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Allospecific Natural Killer Cells by Stimulation Across a Polymorphism of HLA-C

Abstract: The cytotoxicity of human natural killer (NK) cells is modulated by the major histocompatibility complex human leukocyte antigen (HLA)-C molecules on the surface of the target cell. Alloreactive NK cells specific for the NK-1 alloantigen could be reproducibly generated from individuals that were homozygous for HLA-C with asparagine at residue 77 and lysine at residue 80 [HLA-C(Asn77,Lys80)] by stimulation with target cells that were homozygous for HLA-C(Ser77,Asn80); the reciprocal stimulation yielded NK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
3
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(129 citation statements)
references
References 21 publications
2
122
3
2
Order By: Relevance
“…Although it is well known that in HLA-B and -C mismatches are important for the development of GvH disease in allogeneic hematopoietic stem cell transplantation (10, 11), we observed in our experiments that KIR/ligand mismatches in the GvH direction did not lead to increased cytotoxicity of nontransduced NK cells and genetically engineered NK myc-DAP12 donor cells. Hence we assume that our 18-h protocol used for the cytotoxicity assays did not lead to the outgrowth of sufficient alloreactive NK cell numbers needed for induction of potent GvH reactions, which has been reported to require a longer period of time (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well known that in HLA-B and -C mismatches are important for the development of GvH disease in allogeneic hematopoietic stem cell transplantation (10, 11), we observed in our experiments that KIR/ligand mismatches in the GvH direction did not lead to increased cytotoxicity of nontransduced NK cells and genetically engineered NK myc-DAP12 donor cells. Hence we assume that our 18-h protocol used for the cytotoxicity assays did not lead to the outgrowth of sufficient alloreactive NK cell numbers needed for induction of potent GvH reactions, which has been reported to require a longer period of time (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of HLA class I expression (missing self), which is a wellknown characteristic for virally infected and virally transformed tumor cells, dramatically decreases the threshold for NK cell activation (16). NK cells sensing missing self and simultaneously receiving appropriate activating signals, clonally expand (17,18), release cytokines such as IFN-g (5), and kill target cells via the perforin-granzyme pathway (19) or by action of death-receptor ligands (19,20). Although under normal conditions NK cells are unresponsive to self, CAR-engineered NK cells are capable of killing tumor cells expressing the appropriate cell surface Ag.…”
mentioning
confidence: 99%
“…12 The mechanisms used by NK cells to recognize and lyse non-self cells have been studied for several decades. Early in the 1990s, Colonna et al 13 uncovered the alloreactivity potential of NK cells. Using different human leucocyte antigen (HLA)-C haplotype donors and cell lines, they observed that NK cells could expand in mismatched patients.…”
Section: Generalitiesmentioning
confidence: 99%
“…7 The KIR family has been subdivided according to the number of external immunoglobulin (Ig) domains (2D or 3D) and whether they have a long (L) or short (S) cytoplasmic tail that corresponds to their function as inhibitory or activating receptors, respectively (www.ncbi.nlm.nih.gov/PROW). KIRs with two Ig domains (KIR2DL1, KIR2DL2, KIR2DL3) have been shown to interact with specific HLA-C alleles 8,9 and those including three Ig domains (KIR3DL1 and KIR3DL2) to bind with HLA-Bw4 10 and HLA-A3/A11, 11 respectively. Within the human population, the variation of KIR haplotypes mostly depends on the number and type of KIR genes that they inherit.…”
Section: Introductionmentioning
confidence: 99%